Perception of the Quality of Life of Tobacco Growers Exposed to Pesticides: Emphasis on Health, Hearing, and Working Conditions - Cazé, Ana Maria de Barros; Lacerda, Adriana Bender Moreira de; Lüders, Débora; Conto, Juliana De; Marques, Jair; Leroux, Tony (International Archives of Otorhinolaryngology, 2019)
Introduction Tobacco farming exposes workers to various health risks due to the high application of pesticides needed to control pests, weeds and fungal diseases that prevent the tobacco plant growth.Objective To analyze the perception of the quality of life of tobacco growers exposed to pesticides, with emphasis on general health, hearing, and working conditions.Method This is a descriptive, cross-sectional study using a quantitative approach with farmers from southern Brazil. Data were collected from November of 2012 to November of 2014. For data collection, we opted for the 36-item short form health survey (SF-36) questionnaire, and a questionnaire with closed questions about health, hearing and working conditions. We evaluated a total of 78 subjects; the study group, made up of 40 tobacco farmers exposed to pesticides, and a control group of 38 participants without occupational exposure to pesticides. Both groups are residents of the same municipality, and users of the federal public health system.Results The results showed that tobacco growers had lower quality of life scores compared with the control group. Significant differences were observed in the areas of pain and general health. There were correlations between physical elements and chronic diseases; hearing complaints and a lack of personal protective equipment use, occupation and hearing complaints, as well as general health and hearing complaints.Conclusion Tobacco farming is a risky activity for general and hearing health, and it can impact the quality of life of those working in this field.
Keywords: tobacco; pesticides; hearing; quality of life